Enhancing knowledge and worship quality in Muslim patients with diabetic foot ulcer through DiabetEasy - Sadyah, Nur Anna Chalimah; Mulyono, Sri; Satyagraha, Muhammad Thifan (Universitas Muhammadiyah Magelang, 2025)
Diabetic foot ulcers are a complication of diabetes mellitus that can reduce the quality of life, particularly in terms of religious practices for Muslim patients in Indonesia. This program aims to improve knowledge and worship quality in Muslim patients with diabetic foot ulcers through the DiabetEasy program. This program consists of digital health education based on an application and practical worship training for relevant participants at Sultan Agung Islamic Hospital, Semarang, Indonesia. This activity showed increased understanding and worship quality after the intervention, from 60% to 90%. This indicates that this program can improve understanding and worship quality for Muslim patients with diabetic foot ulcers. This program can be an alternative option as a simple non-pharmacological therapy in promotive, preventive, and rehabilitative efforts for the management of diabetic foot ulcers.